(untitled) (African Journal of Science, Technology and Social Sciences, 2024)
Concrete is the major construction material for infrastructure development. Concrete sewer septic tanks are Constructed using the conventional ordinary portland cement (OPC) and the Portland pozzolana cement (PPC). However, OPC based concrete sewer systems are susceptible to biological, mechanical, and chemical degradation. Degradation of the concrete septic leads to their failure hence imposing tremendous environmental problems. The aftermath is the emergence of sanitation-related diseases. The wastewater from failing septic systems leads to contamination of the groundwater or the surface water resulting in the pollution of drinking water. Therefore, the need to explore other possibilities and potential construction materials to achieve sustainable sanitation is inevitable. The use of Limestone Calcined Clay Cement (LC3) in the construction of degradation-resistant concrete sewer septic systems has not been well explored in Kenya. LC3 concrete is resistant to the deterioration effects of aggressive media such as acids, chlorides, and sulfates. This paper presents experimental performance and findings of LC3 in aggressive media vis a vis OPC. The LC3 was formulated by mixing clinker, Calcined clay, limestone, and gypsum at percentages of 50 %, 30 %, 15 %, and 5 % respectively. Compressive strength, Sorptivity, and weight loss during the wet and dry cycles for both LC3 and OPC were evaluated. Simulated concrete septic tanks made of LC3 and OPC were made by casting cubes at water cement ratio of 0.5 and cured in fresh water at ambient temperature for 28 days. These cubes were passed through a regime of W-D cycles in the 3% concentration of Biogenic sulfuric acid. It was observed that after 28 days of curing OPC cubes had slightly higher compressive strength than LC3. However LC3 concrete cubes are expected to have higher compressive strength than the OPC. Cubes curing time increases due to increased pozzolanic activity. Biogenic sulphuric acid attacks on hydrated cement products cause a decrease in compressive strength. The water absorption profile of LC3 cubes was lower as compared to OPC cubes. In conclusion, LC3 cubes had a high potential of resisting degradation as compared to OPC cubes. LC3 show more impressive performance, hence LC3 It’s a potential binder for use in the construction of sewer system. Keywords: Septic tank, Sorptivity, compressive strength, wet-dry cycles, biological, mechanical, and chemical degradation, sustainable sanitation, LC3.